Two approaches for a servomechanism control system using computer vision - João Manuel R. S. Tavares (2004)
In this paper a servomechanism vision control system, based on hand language, is presented. The control images are acquired by a generic webcam and processed, in the working phase, in quasi real time. For this processing, two approaches were considered: in the first one, we used the object control moments to identify the desired order; in the second approach, we used image control orientation histograms. In both approaches, the preset orders images to be considered are acquired in the learning phase. The used servomechanism and the two approaches used for the vision control system are described and some advantages and weakness of each one are indicated. An example of an images control order set, which works satisfactory, is also presented and some conclusions and future work are also addressed.